Clinical predictors of cystic fibrosis chronic rhinosinusitis severity. Issue 7 (4th June 2019) - Zemke, Anna C.; Nouraie, Seyed Mehdi; Moore, John; Gaston, Jordan R.; Rowan, Nicholas R.; Pilewski, Joseph M.; Bomberger, Jennifer M.; Lee, Stella E.
Abstract : Background: Chronic rhinosinusitis (CRS) is a significant manifestation of cystic fibrosis (CF) with wide‐ranging symptom and disease severity. The goal of the study was to determine clinical variables that correlate with outcome measures of disease severity. Methods: A prospective, longitudinal, observational study of 33 adults with symptomatic CRS treated in a CF‐focused otolaryngology clinic was performed. Symptom severity, the presence of rhinosinusitis exacerbations, and endoscopic appearance were assessed, and regression analysis was used to determine clinical predictors of disease outcome. Results: Thirty‐three adults with CF‐CRS were included in the study and followed for a mean of 15 months. Rhinosinusitis exacerbations occurred in 61% of participants during the study, and female sex increased the odds of presenting with an exacerbation visit. Sinus disease exacerbations were associated with an odds ratio of 2.07 for presenting with a pulmonary exacerbation at the next visit. CF‐related diabetes was found to be associated with worse symptoms and endoscopic appearance. Infection with Staphylococcus aureus predicted worsening of symptoms, whereas infections with Pseudomonas aeruginosa improved over time. Allergic rhinitis was associated with worse endoscopic appearance, and nasal steroid use was associated with improved endoscopic appearance. Conclusion: Sex, CF‐related diabetes, sinonasal infection status, allergic rhinitis, and nasal steroid use may all modulate severity of CF‐CRS in adults. Sinusitis exacerbation may be a precursor to pulmonary exacerbation.